Colonic Microbiota Encroachment Correlates With Dysglycemia in Humans - Chassaing, Benoit (Cell Mol Gastroenterol Hepatol, 2017)
BACKGROUND AND AIMS: Mucoid structures that coat the epithelium play an essential role in keeping the intestinal microbiota at a safe distance from host cells. Encroachment of bacteria into the normally almost-sterile inner mucus layer has been observed in inflammatory bowel disease and in mouse models of colitis. Moreover, such microbiota encroachment has also been observed in mouse models of metabolic syndrome, which are associated low-grade intestinal inflammation. Hence, we investigated if microbiota encroachment might correlate with indices of metabolic syndrome in humans. METHODS: Confocal microscopy was used to measure bacterial-epithelial distance of the closest bacteria per high-powered field in colonic biopsies of all willing participants undergoing cancer screening colonoscopies. RESULTS: We observed that, among all subjects, bacterial-epithelial distance was inversely correlated with body mass index, fasting glucose levels, and hemoglobin A(1C). However, this correlation was driven by dysglycemic subjects, irrespective of body mass index, whereas the difference in bacterial-epithelial distance between obese and nonobese subjects was eliminated by removal of dysglycemic subjects. CONCLUSIONS: We conclude that microbiota encroachment is a feature of insulin resistance–associated dysglycemia in humans.